Comparison of MRCP and ERCP in the evaluation of common bile duct and pancreatic duct pathologies - Kumar, Anand; Mohanty, Nihar Ranjan; Mohanty, Madhusmita; Dash, Sashibhusan (Frontiers in Medical Technology, 2023)
Background Magnetic resonance cholangiopancreatography (MRCP) is a non-invasive imaging modality that has high diagnostic accuracy for a wide range of bile duct and pancreatic duct pathologies. Endoscopic retrograde cholangiopancreatography (ERCP) is still the gold standard for the exploration of the biliopancreatic region. Aim The aim of the study was to compare the diagnostic accuracy of MRCP with that of ERCP in the diagnosis of bile duct and pancreatic duct pathologies. Material and methods A total of 60 patients with common bile duct (CBD) and pancreatic duct pathologies detected on MRCP were subsequently evaluated by ERCP in this observational study. A comparison of MRCP findings with ERCP was made. Results MRCP had a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 88.1%, 94.4%, 97.3%, 72.7%, and 90%, respectively, in diagnosing choledocholithiasis in comparison to ERCP. For CBD dilation, the sensitivity was 90.91%, specificity was 93.75% and the PPV, NPV, and accuracy were 97.56%, 78.95%, and 91.67%, respectively, for MRCP. In CBD stricture, MRCP showed a sensitivity, specificity, PPV, NPV, and accuracy of 83.33%, 97.92%, 90.91%, 95.92%, and 95%, respectively. In pancreatic duct dilatation, the sensitivity, specificity, PPV, NPV, and accuracy were all 100%. Pancreatic duct stricture showed a sensitivity, specificity, PPV, NPV, and accuracy of 80%, 98%, 88.89%, 96.08%, and 95%, respectively. For the diagnosis of periampullary carcinoma, the sensitivity, specificity, PPV, NPV, and accuracy rate of MRCP were 80%, 98%, 88.89%, 96.08%, and 95%, respectively. Conclusion No significant difference was found between MRCP and ERCP in diagnosing those six pathologies.